(untitled) - Stoskopf, Michael K (Philadenphia, 1993)
This is one of the textbook of the North Carolina State University College of Veterinary Medicine, Raleigh. Comprehensive introductory textbook for veterinary students. 47 Contributors, predominately U.S. The book is a very thorough review of the diseases affecting fish. This book covers medicine from a taxonomic perspective, grouping diseases by the major taxonomic groups that they affect. One can look up differentials for skin diseases in a certain species without running down the entire list of bacterial, viral, etc.
Keywords: Fish-diseases